Analisis Efektivitas Aplikasi E-Coklit dalam Mendukung Akurasi Data Pemilih pada Pilkada Desa Pasirnagara Tahun 2024 - Ranti Lestari; Asep Nurwanda; Irfan Nursetiawan (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This study aims to analyze the effectiveness of the e-Coklit application in supporting the accuracy of voter data in the 2024 Regional Head Election (Pilkada) in Pasirnagara Village, Pamarican Subdistrict, Ciamis Regency. The research method used is a descriptive qualitative approach with data collected through interviews, observation, and documentation. The study adopts Campbell J. P.’s effectiveness theory, which includes five dimensions: program success, target achievement, program satisfaction, input-output ratio, and overall goal accomplishment. The results indicate that the e-Coklit application is effective in improving voter data accuracy, accelerating the data verification process, and facilitating field officers’ tasks. Despite technical obstacles such as limited internet connectivity and insufficient training, most officers managed to perform well. The e-Coklit application has positively impacted the reduction of duplicate voter records and manual input errors. Therefore, the implementation of e-Coklit supports the achievement of accurate voter data and contributes to strengthening the quality of local democratic processes.